Effects of the Physiological Status and Diet on Blood Metabolic Parameters in Amiata Dairy Donkeys - Federica Salari (MDPI AG, 2021)
Body weight changes and blood metabolic parameters in jennies feeding two different diets and in three physiological statuses were investigated (maintenance vs. pregnancy; maintenance vs. lactation). The relationships between blood metabolic profile and milk quality were also evaluated. Fourteen jennies were allocated to two groups (1: pregnant/lactating; 2: non-pregnant, non–lactating). Pregnant jennies and maintenance jennies (during the first 10-week measurement period) fed a diet consisted of ad libitum grass hay (diet 1); lactating jennies and maintenance jennies (during the last 10-week measurement period) fed ad libitum grass hay plus 2 kg/head/day of concentrate (diet 2). Blood sampling was performed on the jennies of both groups; individual milk samples were also collected during the first 70 days in milk. Higher blood NEFA (p < 0.05) were found in pregnant compared to maintenance jennies (diet 1) (68 vs. 37 μmol/L). Lactating jennies showed higher (p < 0.01) average blood NEFA (268 vs. 26 μmol/L) and glucose (66 vs. 55 mg/dL) compared to the maintenance (diet 2). Blood glucose was positively correlated to milk fat (p < 0.05), while negative significant correlations between de novo milk fatty acids and NEFAs were observed. Positive correlations between plasma B-HBA and somatic cell count (p < 0.01) were also found.